Molecular analysis of chickpea species through molecular markers - Vural, Hasibe Cingilli; Akçin, Abdülkadir (My University, 2010)
Chickpea is an important food legume crop with high nutritional value. Lack of suitable DNA isolation protocol is a limiting factor for any molecular studies on this crop. Today, however, it is possible to determine plants that possess desired qualities in earlier generations using molecular methods (DNA marker techniques) and combine gene areas bearing the desired qualities in commercially used varieties. Therefore, in later studies, 5 ISSR primers, which were pre-determined in chickpea genome mapping and characteristic of resistance, were tested on 10 species (C. arietinum, C. reticulatum, C. pinnatifidum, C. anatolicum, C. echinospermum, C. bijugum, C. Judaicum, C. yamashitae, C. chorassanicum, C. soongaricum) in order to study quantitative traits of the crop, a polymorphism was determined among the species and it was proven that various PCR (Polymerase Chain Reaction) parametres were important in achieving amplification with molecular markers. The present study preferred the ISSR marker because, in studies based on PCR, it is economical and practical to obtain definitive results at the shortest time and such that are being used in routine studies. Besides, the study also found that by virtue of its high incidence of polymorphism and supply of amplification. © 2010 Elsevier B.V., All rights reserved.
Keywords: Chickpea; ISSR; Marker-assisted selection; Molecular marker; RAPD